Quantitative biokinetics of titanium dioxide nanoparticles after oral application in rats: Part 2. Issue 4 (21st April 2017) - Kreyling, Wolfgang G.; Holzwarth, Uwe; Schleh, Carsten; Kozempel, Ján; Wenk, Alexander; Haberl, Nadine; Hirn, Stephanie; Schäffler, Martin; Lipka, Jens; Semmler-Behnke, Manuela; Gibson, Neil
Abstract: The biokinetics of a size-selected fraction (70 nm median size) of commercially available and 48 V-radiolabeled [ 48 V]TiO2 nanoparticles has been investigated in female Wistar-Kyoto rats at retention timepoints 1 h, 4 h, 24 h and 7 days after oral application of a single dose of an aqueous [ 48 V]TiO2 -nanoparticle suspension by intra-esophageal instillation. A completely balanced quantitative body clearance and biokinetics in all organs and tissues was obtained by applying typical [ 48 V]TiO2 -nanoparticle doses in the range of 30–80 μgkg −1 bodyweight, making use of the high sensitivity of the radiotracer technique. The [ 48 V]TiO2 -nanoparticle content was corrected for nanoparticles in the residual blood retained in organs and tissue after exsanguination and for 48 V-ions not bound to TiO2 -nanoparticles. Beyond predominant fecal excretion about 0.6% of the administered dose passed the gastro-intestinal-barrier after one hour and about 0.05% were still distributed in the body after 7 days, with quantifiable [ 48 V]TiO2 -nanoparticle organ concentrations present in liver (0.09 ngg −1 ), lungs (0.10 ngg −1 ), kidneys (0.29 ngg −1 ), brain (0.36 ngg −1 ), spleen (0.45 ngg −1 ), uterus (0.55 ngg −1 ) and skeleton (0.98 ngg −1 ). Since chronic, oral uptake of TiO2 particles (including a nano-fraction) by consumers has continuously increased in the past decades, the possibility of chronic accumulation of such biopersistent nanoparticles in secondary organs and the skeleton raises questions about the responsiveness of their defense capacities, and whether these could be leading to adverse health effects in the population at large. After normalizing the fractions of retained [ 48 V]TiO2 -nanoparticles to the fraction that passed the gastro-intestinal-barrier and reached systemic circulation, the biokinetics was compared to the biokinetics determined after IV-injection (Part 1). Since the biokinetics patterns differ largely, IV-injection is not an adequate surrogate for assessing the biokinetics after oral exposure to TiO2 nanoparticles.